Efficiency and spatial resolution of the CASCADE thermal neutron detector - Köhli, Markus; Allmendinger, Fabian; Häußler, W.; Schröder, T.; Klein, M.; Meven, M.; Schmidt, Ulrich (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
We report on the CASCADE project - a detection system, which has been designed for the purposes of neutron Spin Echo spectroscopy and which is continuously further developed and adapted to various applications. It features 2D spatially resolved detection of thermal neutrons at high rates. The CASCADE detector is composed of a stack of solid 10B coated Gas Electron Multiplier foils, which serve both as a neutron converter and as an amplifier for the primary ionization deposited in the standard counting gas environment. This multi-layer setup efficiently increases the detection efficiency and by extracting the signal of the charge traversing the stack the conversion layer can be identified allowing a precise determination of the time-of-flight. The spatial resolution is found by optical contrast determination to be σ=(1.39±0.05)mm and by divergence corrected aperture measurements σ=(1.454±0.007)mm, which is in agreement with the simulated detector model. Furthermore this enabled to investigate and describe the non-Gaussian resolution function. At the HEiDi diffractometer the absolute detection efficiency has been studied. At 0.6Å for the 6 layer detector, which is currently part of the RESEDA spectrometer, an efficiency of 7.8% has been measured, which by means of Monte Carlo simulations translates to (21.0±1.5)% for thermal neutrons at 1.8Å and (46.9±3.3)% at 5.4Å.
Gesehen am 06.05.2020